Laparoscopic Witzel jejunostomy - Lotti, Marco (J Minim Access Surg, 2021)
The placement of a feeding jejunostomy can be indicated in malnourished patients with gastric and oesophagogastric junction cancer to allow for enteral nutritional support. In these patients, the jejunostomy tube can be suitably placed at the time of staging laparoscopy. Several techniques of laparoscopic jejunostomy (LJ) have been described, yet the Witzel approach remains neglected, due to the perceived difficulty of suturing the bowel around the tube and securing them to the abdominal wall. Here, we describe a novel technique for LJ, using a single barbed suture for securing the bowel and tunnelling the jejunostomy catheter according to the Witzel approach.